The Impact of Workload, Productivity, and Social Support on Burnout Among Marketing Faculty During the COVID-19 Pandemic. (August 2022) - Taylor, David G.; Frechette, Michael
The COVID-19 pandemic was an unprecedented event in modern history, transforming the nature of higher education. As course delivery moved online, marketing educators were faced with higher workloads and more demands on their time. Anecdotal evidence suggested that faculty were working more, and as the 2020–2021 school year progressed, reports of fatigue and burnout were prevalent. An empirical study measures the perceived increases in workload among marketing faculty and the outcomes of that work, as well as levels of burnout. In addition, a model of burnout antecedents is proposed and tested. On average, marketing educators experienced moderate levels of burnout, which was increased by work demands in research and teaching, as well as student interaction, whereas research productivity decreased burnout. Burnout was not influenced by gender, rank, tenure status, or institution type.